Oedipus’ moral responsibility in Sophocles’ Oedipus tyrannus (2017)
This paper critically examines the issues of moral responsibility in Sophocles' Oedipus Tyrannus. This play has generated different interpretations from Greek antiquity till now. Attempts have been mode to decide Oedipus’ moral standing, which has equally brought about different analysis, one of which considers Oedipus guilty of patricide and incest and holds him responsible for his actions. Other interpretations see Oedipus as a mere puppet in the hands of the gods. Generally, the tragic play of Sophocles, like other Greek myths, presents man as having no power or self-will to control his life events; he does not have the capability to exercise his free will. From the start of the play, the Greek god Apollo plays a vital role of ensuring the fulfillment of Oedipus ' destiny by his interference through oracl.es. This notion has led to the question of whether Oedipus is morally responsible for the events of his life or not. Therefore, this study subjects Oedipus Tyrannus to literary analysis in order to address this issue